Global Economic Dynamics and Its Impact on Indonesian Trade: Multi-Regional Input-Output Analysis Approach - Annisa Muthi Zajidah; Dyah Widyastuti; Immanuel Nicholas Fransepta Samosir; Patrick Noel Simamora; Fitri Kartiasih (Cendekia Niaga, 2025)
This study investigates the impact of economic dynamics on international trade using a multiregional analysis of Input-Output table. Multiplier effect analysis is used to study how a sector affects both the domestic economy and the economies of partner countries. Employing forward linkage and backward linkage values to analyze the linkages, determine which sectors are superior in international trade operations. The impact of partner countries' economies on Indonesia's economy is then simulated. The results show that Indonesia tends to rely on imports and exports connected to manufacturing. The manufacturing, chemical and chemical goods, and paper and printing industries are the main drivers of foreign trade. Furthermore, when Indonesia goes through a recession, the ASEAN nations typically have a big influence on the national economy. So economic diversification, domestic consumption stimulus, and building economic resilience are needed.